The judicial process in the area of domestic violence - Pérez-Jiménez, María Fátima (My University, 2017)
The intervention of the criminal justice system in the area of gender-based violence has an important place in the legislative and institutional structure. With it the society provides a framework for prevention and especially towards protection of the female-victim. Using a qualitative methodology, this paper explores the experiences of fifteen women during the process of the criminal justice system. It shows how the victims experience the recomended protection that the criminal law tries to give them. Research findings reflect the particularities of the institutional treatment dispensed to the victims through the encounter with different legal actors. We discuss current controversies concerning the judicial approach to domestic violence and make sugestions in the movement to address domestic violence through the criminal justice system.
Keywords: Violencia familiar; Domestic violence; Judicial process